Presenting your findings: a practical guide for creating tables - Nicol, Adelheid A. M. (American Psychological Association, 2010)
Introduction -- Frequency and demographic -- Means -- Chi-square -- Test of means -- Post hoc -- Correlation -- Canonical correlation -- Analysis of variance -- Multivariate analysis of variance -- Analysis of covariance -- Multivariate analysis of covariance -- Cluster -- Log-linear -- Discriminant function analysis -- Factor analysis -- Multiple regression -- Logistic regression -- Confirmatory factor analysis -- Structural equation modeling -- Meta-analysis -- Word tables